2019
DOI: 10.1364/oe.27.015327
|View full text |Cite
|
Sign up to set email alerts
|

Improving near-eye display resolution by polarization multiplexing

Abstract: We present here an optical approach to boost the apparent pixel density by utilizing the superimposition of two shifted-pixel grids generated by a Pancharatnam-Berry deflector (PBD). The content of the two shifted pixel grids are presented to the observer's eye simultaneously using a polarization-multiplexing method. Considering the compact and lightweight nature of PBD, this approach has potential applications in near-eye display systems. Moreover, the same concept can be extended to projection displays with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…As another important physical property of light, polarization specifies the geometrical orientation of electromagnetic wave oscillations. Utilizing the polarization state of light has played a pivotal role in numerous applications, including telecommunications 53 55 , imaging 56 – 61 , sensing 62 64 , computing 65 , and displays 66 , 67 . For example, polarization-division multiplexing (PDM) has been used in telecommunication systems to permit two channels of information to be simultaneously transmitted using orthogonal polarization states over a single wavelength 54 , 68 .…”
Section: Introductionmentioning
confidence: 99%
“…As another important physical property of light, polarization specifies the geometrical orientation of electromagnetic wave oscillations. Utilizing the polarization state of light has played a pivotal role in numerous applications, including telecommunications 53 55 , imaging 56 – 61 , sensing 62 64 , computing 65 , and displays 66 , 67 . For example, polarization-division multiplexing (PDM) has been used in telecommunication systems to permit two channels of information to be simultaneously transmitted using orthogonal polarization states over a single wavelength 54 , 68 .…”
Section: Introductionmentioning
confidence: 99%
“… Lee et al, 2017b demonstrated an optical wobulation VR system by synchronizing a switchable liquid crystal (LC) Pancharatnam-Berry phase deflector and subframe images, increasing the pixel density through time multiplexing. Zhan et al., 2019b , further advanced this approach using a passive polymer deflector and a polarization management layer, doubling the apparent pixel density without reducing the original frame rate. More recently, Nguyen et al., 2020 realized mechanical wobulation for both micro-OLED and LCD panels to reduce the screen-door effect.…”
Section: Vr: Resolutionmentioning
confidence: 99%
“…For instance: Y. Lee, et al used Pancharatnam-Berry deflectors and lenses to enable a compact and lightweight near-eye display system with depth adaption [7]; Y. Weng, et al demonstrated polarization volume grating based couplers for waveguide display to realize a full-color near-eye display [8]; K. Gao, et al built high efficiency beam steering devices with ultra-large deflection angle [9]. Among all photonics devices, liquid-crystal-based geometric phase elements and polarization volume holograms have been extensively studied and applied to AR/VR optical systems most recently [7][8][9][10][11]. Geometric phase elements split linear or un-polarized beams into two orthogonal circular polarizations with symmetric deflecting directions.…”
Section: Benefits Of Liquid Crystal Photonics For Ar/vrmentioning
confidence: 99%